Investment pattern in rural households of Ollukkara Block Panchayath in Thrissur District - Pratheesh V.S (Department of Agricultural Economics, College of Horticulture, 2002)
Agriculture which is the back bone of Indian economy, is now heading towards a radical transformation. When the green revolution technology was introduced in the mid sixties, great expectations were raised as to the beneficial effects it could induce into every class of farmers and other sectors of the populations by increasing food production, employment opportunities and income levels. But its latter day performances have belied these expectations and it seemed that only those who have necessary absorptive capacity or infrastructure are only benefited. So for the betterment of agriculture there should be more and more investment both in the public and private sector. Under these circumstances the present study entitled "Investment Pattern in rural households of Ollukkara block panchayath in Thrissur district" is of high relevance and was conducted with the following objectives. 1. To study the different sources of income of rural people 2. To examine the savings and expenditure pattern 3. To analyze the nature of investment 4. To identify the constraints associated with investment in rural areas. The study was conducted in the sample selected at random from 50 numbers of Agricultural labourers, farmers and service sector people from the five wards selected from the total 74 wards in the Ollukkara block panchayath of Thrissur district. The data for the agricultural year 2001-2002 were collected using a well structured interview schedule. The study revealed that the mainsource of farm income in farmers and service sector people was crops where as for labourers it was livestock. On an average 81. 9 5 per cent of the total farm income was directed from the crops and only 18,95 was from livestock. Category wise analysis showed that net income and benefit cost ratio were much higher for labourer households and lowest for service sector people.